Structural behavior of concrete-filled steel tube short columns stiffened by external and internal continuous spirals. (December 2019) - Alrebeh, Salih K.; Ekmekyapar, Talha
Abstract: Concrete-filled steel tube (CFST) column is one of the most effective forms of composite members in which the steel tube provides both axial strength and confining pressure to improve the compressive capacity and the ductility of the core concrete. This paper presents an evaluation of the structural behavior of CFST short columns strengthened by external and internal continuous spirals. A total of 16 CFST specimens were tested under axial compression. Specimens were stiffened as follows: (1) external continuous spiral (ECS) welded to the exterior surface of the steel tube, (2) internal continuous spiral (ICS) welded to the interior surface of the steel tube, and (3) unwelded internal continuous spiral (UICS) placed longitudinally inside the steel tube. Self-compacting concrete (SCC) was used in the experimental study. The main parameters in this study are the diameter of spiral bar, the number of spiral turns, and the location of the continuous spiral. From the test results, it was concluded that toughness, elastic strength, and ductility were improved significantly as a result of stiffening the CFST columns by external and internal spirals. ECS, ICS, and UICS improved the compression capacity up to 46.8%, 48.7%, and 47.9%, respectively, as compared with the control specimen. A theoretical model to estimate the ultimate load of stiffened CFST columns was developed and close correlations were found between the model and the experimental results.